Immunity and Growth Plasticity of Asian Short-Toed Lark Nestlings in Response to Changes in Food Conditions: Can It Buffer the Challenge of Climate Change-Induced Trophic Mismatch? - Guang Lu; Xinjie Zhang; Xinyu Li; Shuping Zhang (Animals, 2023)
Passerine nestlings frequently suffer from sub-optimal food conditions due to climate change-induced trophic mismatch between the nestlings and their optimal food resources. The ability of nestlings to buffer this challenge is less well understood. We hypothesized that poor food conditions might induce a higher immune response and lower growth rate of nestlings, and such physiological plasticity is conducive to nestling survival. To test this, we examined how food (grasshopper nymphs) abundance affects the expression of interferon-γ (IFN-γ), tumor necrosis factor-α (TNF-α), interleukin-1 β (IL-1β) genes, plasma IGF-1 levels, body mass, and fledging rates in wild Asian short-toed lark (Alaudala cheleensis) nestlings. Linear mixed models revealed that nymph biomass significantly influenced the expression of IFN-γ, TNF-α, and IL-1β genes, and the level of plasma IGF-1. The expressions of IFN-γ, TNF-α, and IL-1β genes were negatively correlated with nymph biomass and plasma IGF-1 level. Plasma IGF-1 level, nestling body mass growth rate, was positively correlated with nymph biomass. Despite a positive correlation between the nestling fledge rate and nymph biomass, more than 60% of nestlings fledged when nymph biomass was at the lowest level. These results suggest that immunity and growth plasticity of nestlings may be an adaptation for birds to buffer the negative effects of trophic mismatch.